Exposure to air pollutants contributes to increased rate of neovascular age-related macular degeneration in Israel - Alon Sela; Rinat Levinshtein; Shiri Shulman (PLoS ONE, 2025)
Age-related macular degeneration (AMD) is a multi-factorial degenerative disease of the retina and the leading cause for vision loss in the developed world. Air pollution is considered the greatest environmental threat to public health globally. Accumulating evidence indicates that air pollution may be a modifiable risk factor for chronic eye diseases of the lens and retina, including AMD. We examined the concentration of seven air pollution particles and their influence on the prevalence of neovascular AMD in Israel. Records of patients with AMD between 2016 and 2019 were crossed with their residential areas and correlated with pollution data. AMD rates were correlated with 5 types of gas: nitrogen dioxide (NO2), nitrogen oxide (NO), carbon monoxide (CO), ozone (O3), sulphur dioxide (SO2), and particulate matter - PM2.5 and PM10. A total of 93 localities across Israel were included in the analysis. AMD rates were higher in localities with greater air pollution. NO2, NOx, and PM2.5 were positively correlated with AMD rates, while O3 was negatively correlated with AMD rates. However, analysis of the effect of all air pollutant particles combined, showed a complex and highly non-linear effect on AMD rate, with the strongest non-linearity observed for carbon monoxide. NO2, NOx, and PM2.5 contribute to higher rate of AMD in Israel while O3 seems to have a protective role (probably due to ultraviolet filtering) on AMD rates. The interaction between air pollutants and AMD seems to be complex and non-linear and should be further studied.